Menelusuri Akar Historis Dan Faktor Pendorong Lahirnya Studi Perbandingan Administrasi Negara: Dari Paradigma Klasik Ke Era Global Governance - Mozin, Sri Yulianty; Badjuka, Alexander H.; Lawani, Zaskia Shalwa; Liputo, Nadila; Ramadhani, Rini; Pulanding, Fatralisa D. (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This study aims to explore the historical roots and driving factors behind the emergence of Comparative Public Administration (CPA) and its relevance within the context of contemporary global governance. Employing a qualitative-descriptive approach through a comprehensive literature review, the research analyzes the paradigm shifts in public administration from the classical era to the modern governance period. The findings indicate that CPA emerged as a response to the limitations of the Western-centric and universalistic classical administrative theories. Factors such as decolonization, modernization, and globalization served as major catalysts for developing a more contextual and adaptive approach to public administration in developing countries. Scholars such as Fred W. Riggs, Ferrel Heady, and Dwight Waldo played pivotal roles in expanding CPA’s analytical scope from structural perspectives to ecological and network-oriented analyses. The study concludes that CPA is not merely a descriptive tool for comparing bureaucratic systems but also a reflective framework for reinterpreting classical bureaucratic values, rationality, efficiency, and accountability, within the complex dynamics of global governance. Thus, CPA holds strategic importance in bridging classical public administration theories with the adaptive governance demands of the globalization and digitalization era.